2019
DOI: 10.3390/su11092456
|View full text |Cite
|
Sign up to set email alerts
|

Nitrified Human Urine as a Sustainable and Socially Acceptable Fertilizer: An Analysis of Consumer Acceptance in Msunduzi, South Africa

Abstract: Sustainable smallholder farming is contingent on fertilizer access. Soils across Africa are typically nutrient deficient, a condition exacerbated by long-term nutrient mining. Nitrified urine fertilizer is a nutrient-rich and hygienically safe solution derived from human urine. It has the potential to provide a sustainable source of soil nutrients to low and middle-income countries struggling with food insecurity challenges. This study presents findings of a survey that assessed public acceptance within Msundu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Younger respondents and those who resided in rural parts of the municipality were "most receptive to the use of nitrified urine fertilizer" compared to their older and urban counterparts. Unlike previous studies, which advanced religion and culture as underpinning factors for the acceptability of the use of nitrified urine fertilizer [3,33,36,37], the study by Wilde et al [35] found that respondents distrusted the technology involved in the treatment process. The authors, therefore, concur with the view that "behavior towards sanitation and excrement is a complex interaction between individual and societal norms and is often not based on scientific logic or knowledge" [35].…”
Section: Barriers To the Acceptance Of Human Excreta Reuse In Agriculturementioning
confidence: 81%
See 2 more Smart Citations
“…Younger respondents and those who resided in rural parts of the municipality were "most receptive to the use of nitrified urine fertilizer" compared to their older and urban counterparts. Unlike previous studies, which advanced religion and culture as underpinning factors for the acceptability of the use of nitrified urine fertilizer [3,33,36,37], the study by Wilde et al [35] found that respondents distrusted the technology involved in the treatment process. The authors, therefore, concur with the view that "behavior towards sanitation and excrement is a complex interaction between individual and societal norms and is often not based on scientific logic or knowledge" [35].…”
Section: Barriers To the Acceptance Of Human Excreta Reuse In Agriculturementioning
confidence: 81%
“…In a study by Mariwah and Drangert [28], it was noted that 97% of the participants were of the view that human excreta possess health risks. Another concern in South Africa is about the possible presence of menstrual blood in urine and the transmission of HIV/AIDS through urine [36].…”
Section: Barriers To the Acceptance Of Human Excreta Reuse In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The other one is represented by consumer contribution in adopting sustainable product options. Most often, convincing consumers to consider sustainable products, such as bio-pesticides or natural fertilizers, requires extended research efforts to understand their needs, motivations, or hindering factors [63][64][65]. Conventional pesticides are considered efficient by 81.7% of interviewed farmers (Table 2), which can become a hindering factor for the transition to bio-pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Other site-specific social studies conducted across the globe on urine diversion have emphasized different facets of the complex risks and understandings caught up in both the technological implementation and agricultural reuse of human urine. These have included research with diverse communities such as general public perspectives in South Africa (Wilde et al, 2019); farmers, college students, and consumers in Switzerland (Lienert et al, 2003;Lienert et al, 2006;Pahl-Wostl et al, 2003); and pilot implementations in university settings and villages in Australia (Abeysuriya et al, 2013;Cook et al, 2013). These studies have been focused on behavioral and attitudinal approaches of specific stakeholder groups.…”
Section: Introductionmentioning
confidence: 99%